Neural Precursor Cell Transplantation Enhances Functional Recovery and Reduces Astrogliosis in Bilateral Compressive/Contusive Cervical Spinal Cord Injury - Wilcox, Jared T. (AlphaMed Press, 2014)
Spinal cord injury has a significant societal and personal impact. Although the majority of injuries involve the cervical spinal cord, few studies of cell transplantation have used clinically relevant models of cervical spinal cord injury, limiting translation into clinical trials. Given this knowledge gap, we sought to examine the effects of neural stem/precursor cell (NPC) transplants in a rodent model of bilateral cervical contusion-compression spinal cord injury. Bilateral C6-level clip contusion-compression injuries were performed in rats, which were then blindly randomized at 2 weeks after injury into groups receiving adult brain-derived NPCs, vehicle, or sham operation. Long-term survival of NPCs was evident at 10 weeks after transplant. Cell grafts were localized rostrocaudally surrounding the lesion, throughout white and gray matter. Graft-derived cells were found within regions of gliotic scar and motor tracts and deposited myelin around endogenous axons. The majority of NPCs developed an oligodendroglial phenotype with greater neuronal profiles in rostral grafts. Following NPC transplantation, white matter was significantly increased compared with control. Astrogliosis and glial scar deposition, measured by GFAP-positive and chondroitin sulfate proteoglycan-positive volume, was significantly reduced. Forelimb grip strength, fine motor control during locomotion, and axonal conduction (by in vivo electrophysiology) was greater in cell-treated animals compared with vehicle controls. Transplantation of NPCs in the bilaterally injured cervical spinal cord results in significantly improved spinal cord tissue and forelimb function, warranting further study in preclinical cervical models to improve this treatment paradigm for clinical translation.